Thermal equilibration of iron meteorite and pallasite parent bodies recorded at the mineral scale by Fe and Ni isotope systematics. (15th November 2017) - Chernonozhkin, Stepan M.; Weyrauch, Mona; Goderis, Steven; Oeser, Martin; McKibbin, Seann J.; Horn, Ingo; Hecht, Lutz; Weyer, Stefan; Claeys, Philippe; Vanhaecke, Frank
Abstract: In this work, a femtosecond laser ablation (LA) system coupled to a multi-collector inductively coupled plasma-mass spectrometer ( fs -LA-MC-ICP-MS) was used to obtain laterally resolved (30–80 μm), high-precision combined Ni and Fe stable isotope ratio data for a variety of mineral phases (olivine, kamacite, taenite, schreibersite and troilite) composing main group pallasites (PMG) and iron meteorites. The stable isotopic signatures of Fe and Ni at the mineral scale, in combination with the factors governing the kinetic or equilibrium isotope fractionation processes, are used to interpret the thermal histories of small differentiated asteroidal bodies. As Fe isotopic zoning is only barely resolvable within the internal precision level of the isotope ratio measurements within a single olivine in Esquel PMG, the isotopically lighter olivine core relative to the rim (Δ 56/54 Ferim-core  = 0.059‰) suggests that the olivines were largely thermally equilibrated. The observed hint of an isotopic and concentration gradient for Fe of crudely similar width is interpreted here to reflect Fe loss from olivine in the process of partial reduction of the olivine rim. The ranges of the determined Fe and Ni isotopic signatures of troilite (δ 56/54 Fe of −0.66 to −0.09‰) and schreibersite (δ 56/54 Fe of −0.48 to −0.09‰, and δ 62/60 Ni of −0.64 to +0.29‰) may result from thermal equilibration. Schreibersite and troilite likely remained in equilibrium with their enclosing metal to temperatures significantly below their point of crystallization. The Ni isotopic signatures of bulk metal and schreibersite correlate negatively, with isotopically lighter Ni in the metal of PMGs and isotopically heavier Ni in the metal of the iron meteorites analyzed. As such, the light Ni isotopic signatures previously observed in PMG metal relative to chondrites may not result from heterogeneity in the Solar Nebula, but rather reflect fractionation in the metal-schreibersite system. Comparison between the isotope ratio profiles of Fe and Ni determined across kamacite-taenite interfaces (Δ 56/54 Fekam-tae  = −0.51 to −0.69‰ and Δ 62/60 Nikam-tae  = +1.59 to +2.50‰) and theoretical taenite sub-solidus diffusive isotopic zoning broadly constrain the cooling rates of Esquel, CMS 04071 PMGs and Udei Station IAB to between ∼25 and 500 °C/Myr.